2019
DOI: 10.1002/jcp.29264
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐20a‐containing exosomes from umbilical cord mesenchymal stem cells alleviates liver ischemia/reperfusion injury

Abstract: Mesenchymal stem cells (MSCs) have been proved to exert considerable therapeutic effects on ischemia‐reperfusion (I/R)‐induced injury, but the underlying mechanism remains unknown. In this study, we aimed to explore the potential molecular mechanism underlying the therapeutic effect of MSCs‐derived exosome reinforced with miR‐20a in reversing liver I/R injury. Quantitative real‐time polymerase chain reaction, Western blot, and IHC were carried out to compare the differential expressions of miR‐20a, Beclin‐I, F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(51 citation statements)
references
References 47 publications
0
50
0
1
Order By: Relevance
“…Previous MSC therapies have reported the selective homing of administered MSCs to the site of injury [22,39], consistent with our results showing the preferential engraftment of hEPO-MPs and their EPO mRNA contents to the inflammatory site of kidney injury, making this delivery platform highly attractive. Gene overexpression has been shown to enhance the therapeutic efficacy of MSC-derived MPs in various disease models [29,30]; therefore, using hEPO-MPs as a therapeutic strategy may be more convenient as well as physiologically relevant than systemic rhEPO administration. To our knowledge, our findings are the first to demonstrate that genetically modified hEPO-MPs could be used as a novel therapeutic agent to inhibit renal fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous MSC therapies have reported the selective homing of administered MSCs to the site of injury [22,39], consistent with our results showing the preferential engraftment of hEPO-MPs and their EPO mRNA contents to the inflammatory site of kidney injury, making this delivery platform highly attractive. Gene overexpression has been shown to enhance the therapeutic efficacy of MSC-derived MPs in various disease models [29,30]; therefore, using hEPO-MPs as a therapeutic strategy may be more convenient as well as physiologically relevant than systemic rhEPO administration. To our knowledge, our findings are the first to demonstrate that genetically modified hEPO-MPs could be used as a novel therapeutic agent to inhibit renal fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous MSC therapies have reported the selective homing of administered MSCs to the site of injury [22,39], consistent with our results showing the preferential engraftment of hEPO-MPs and their EPO mRNA contents to the in ammatory site of kidney injury, making this delivery platform highly attractive. Gene overexpression has been shown to enhance the therapeutic e cacy of MSC-derived MPs in various disease models [29,30]; therefore, using hEPO-MPs as a therapeutic strategy may be more convenient as well as physiologically relevant than systemic rhEPO administration. To our knowledge, our ndings are the rst to demonstrate that genetically modi ed hEPO-MPs could be used as a novel therapeutic agent to inhibit renal brosis.…”
Section: Discussionmentioning
confidence: 99%
“…Since MP characteristics depend on the cell of origin and the external stimuli or injury, recent studies have used preconditioning or gene modi cation to enhance the therapeutic e cacy of MSC-derived MPs [26]. In particular, MPs derived from hypoxia-preconditioned MSCs promoted angiogenesis more than those derived from MSCs cultured under normoxic conditions [27,28], while gene overexpression enhanced the therapeutic e cacy of MSCderived MPs in various disease models [29,30]. Therefore, using MPs derived from EPO mRNA-overexpressing MSCs could be an appealing therapeutic strategy to effectively deliver EPO mRNA to target cells and promote tissue repair or regeneration.…”
Section: Kmsc-mps Carried Proangiogenic Signals and Ameliorated Peritmentioning
confidence: 99%
“…Exosomes from miR-223-overexpressing MSCs downregulated NLRP3 and caspase-1, and exhibited protective effects in injured hepatocytes and an experimental autoimmune hepatitis model [160]. Another study showed that exosomes from miR-20a-overexpressing MSCs downregulated beclin-I and FAS, and alleviated apoptosis and autophagy in a liver ischemia-reperfusion rat model [161]. In LPS-induced alveolar epithelial cells, exosomes from miR-30b-3p-overexpressing MSCs promoted cell proliferation and diminished cell apoptosis by downregulating SAA3.…”
Section: Gene Overexpression To Improve the Function Of Msc-derived Ementioning
confidence: 99%